Digitalization of MSMEs In Palembang City: Development of A Web-Based Cash Recording Application With Multitenancy Architecture - Abiyasa Eka Saputra (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Palembang City face challenges in recording financial transactions, which are generally still done manually with books and papers or often not recorded at all. This leads to a lack of transparency in financial management, making it difficult for MSMEs to know the available cash balance as well as their real-time income and expenditures. This research aims to develop a web-based cash recording application that can be accessed through smartphones, utilizing Laravel and React.js technology with a multitenancy architecture. The multitenancy architecture allows one application to be used by multiple MSMEs with secure and efficient data isolation. The research results indicate that the developed application can enhance the efficiency of transaction recording and provide better visibility of the financial condition of MSMEs. With this implementation, MSMEs can record transactions in real-time, improve the accuracy of financial data, and support better business decision-making.